Gender-based study of paired monophthongs: a sociophonetics approach - Safeer, Nadia; Anjum, Uzma; Saleem, Tahir (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study investigates gender-based phonological variations in the acoustic production of paired monophthongs among Pahari native speakers of Pakistani English (PakE). It addresses the research questions concerning how male and female speakers differ in the acoustic characteristics of English monophthongs within the PakE context. The study builds upon the theoretical frameworks of acoustic phonetics and sociophonetics, combining them to analyse vowel acoustics while considering sociocultural influences precisely. Ten participants, evenly divided between males and females, provided speech samples for specific monophthong pairs. A standardised list of 10 monosyllabic words in pairs was used as stimuli. The analysis of collected speech samples employed Praat software for formant and duration measurements, facilitated by R Software for graphical representation. Results indicate that male speakers exhibit higher F1 and F2 values in several monophthong pairs, while female speakers tend to have longer durations. These gender-related phonological distinctions contribute to understanding PakE's phonological landscape, bridging the gap between language, gender, and social identity. The study has implications for pronunciation teaching and speech technology in PakE, offering a nuanced exploration of the sociophonetic dynamics at play. Future research can delve further into sociolinguistic factors influencing these phonological distinctions and their social motivations. This research enhances the academic understanding of PakE's phonological complexity and practical applications in language pedagogy and speech technology.